GROSS MORPHOLOGICAL AND MORPHOMETRIC STUDIES ON THE STERNUM OF VICTORIAN CROWNED PIGEON (Goura victoria) - O.R. Sathyamoorthy; K. Nagarajan; Sabiha Hayath Basha; S. Ushakumary (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The sternum of the Victorian crowned pigeon (Goura victoria) was a long (10.40cm), and triangular bone. The dorsal surface was deeply concave and showed very large foramina behind the cranial border in the centre. The dorsal surface showed a groove in the centre, which contained numerous small pneumatic foramina. The cranial border was thick, convex and narrow. Below the dorsal ridge of cranial border, a large, round pneumatic foramen was present. The sternal spine was rudimentary. The craniolateral processes were 1.0 cm long, thick, pneumatised, projected upwards and cranially. The lateral borders contained three articular cylinders for the sternal ribs and the troughs between them contained pneumatic foraminae. The thoracic processes were large, well developed and scythe-shaped. The caudolateral processes were 1.5cm long, thin and projected caudally. It enclosed along with the lateral borders of the corpus sterni, a triangular notch, an incisura ovalis. The caudal border of the corpus sterni was very narrow (0.5cm), convex and should be ended as blunt. The sternal crest was large and triangular in shape. It began from below the ventral ridge of the cranial border extended deeply ventrally, formed a gentle curve in the cranial half and a steep curve in the caudal half and reached up to the caudal border of the corpus sterni. It was 11.50 cm long and the height of the sternal crest between the midpoint of the cranial border of the sternum and the highest point of the sternal crest (H) was 6.10cm.